Analisis Pengaruh Volume Lalulintas Terhadap Tingkat Kebisingan Kawasan Jalan Sungai Saddang Lama - Tjandra, Jericho; Thioritz, Stevy; Mursalim (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Atma Jaya Makassar, 2024)
As the population increases and economic development certainly causes an increase in traffic volume in an urban area, and also of course every vehicle produces noise, each noise depends on each type of vehicle used. This study discusses the effect of traffic volume on the noise level of traffic activities that occur in the Jalan Sungai Saddang Lama area which aims to determine the average value of noise that occurs in 1 day or 24 hours and conduct hypothesis testing between day and night noise levels. This research was conducted using a digital sound level meter as a measure of noise and traffic counter application as a counter of the number of vehicles traveling, while the software used to test the hypothesis is Matlab. The results showed that the equivalent noise level produced by vehicles in the area of Sungai Saddang Lama Road averaged around 78,1dbA, and the relationship between the effect of traffic volume and noise level was stated to have a very strong relationship for the first day, while the second day was stated to have a fairly strong relationship and the third day was stated to have a very strong relationship. Hypothesis testing is done by comparing 2 variables, namely between noise levels during the day and night with their respective classifications, then the results of the hypothesis test H = 0 are accepted as many as 10, while H = 1 is accepted as many as 6.